Are We Speaking the Same Language? The Experiences of International Students and Scholars in North American Higher Education. Issue 2 (3rd July 2019) - Sharaievska, Iryna; Kono, Shintaro; Mirehie, Mona Sadat
Abstract: More than a million international students studied at U.S. colleges and universities in 2016–2017 (Open Doors Report, 2017), bringing close to 39 billion dollars into the U.S. economy (U.S. Department of Commerce, 2017). Previous research reveals that international students often face significant obstacles in their adjustment with the U.S. education system, cultural differences, language barriers, and social isolation. This article adopts a social constructionism approach to discuss the experiences of international students in North America from the perspective of three individuals who graduated from North American universities within the last six years. Issues of cultural, linguistic, structural, and social barriers experienced by international students are discussed. Moreover, practical suggestions based on personal experiences of the authors are provided to prepare prospective international students and scholars entering the North American education system for the challenges they may encounter.